Chronic NaAsO2 exposure promotes migration and invasion of prostate cancer cells by Akt/GSK-3β/β-catenin/TCF4 axis-mediated epithelial-mesenchymal transition - Zhi-Hui Zhang; Hai-Xin Yan; Ming-Dong Liu; Feng-Wen Niu; Kai Yao; Shi-Yao Feng; Xi Li; Yuan-Hua Chen; Dong-Dong Xie (Ecotoxicology and Environmental Safety)
Inorganic arsenic is a Class I human Carcinogen. However, the role of chronic inorganic arsenic exposure on prostate cancer metastasis still unclear. This study aimed to investigate the effects and mechanism of chronic NaAsO2 exposure on migration and invasion of prostate cancer cells. DU145 and PC-3 cells were exposed to NaAsO2 (2 μM) for 25 generations. Wound healing and Transwell assays showed that chronic NaAsO2 exposure promoted migration and invasion of DU145 and PC-3 cells. In addition, chronic NaAsO2 exposure induced epithelial-mesenchymal transition (EMT) of DU145 cells by promoting β-catenin/TCF4 transcriptional activity. Mechanically, NaAsO2 promoted GSK-3β inactivation in the ''disruption complex'' through Akt- mediated phosphorylation at serine 9, and then inhibited the phosphorylation and ubiquitination degradation of β-catenin, which led to its nuclear translocation. Ly294002, a selective phosphatidylinositol 3-kinase (PI3K)/Akt inhibitor, suppressed the β-catenin/TCF4 complex activation and EMT through blocking Akt-mediated GSK-3β inactivation in the ''disruption complex'' in chronic NaAsO2 exposed DU145 and PC-3 cells. Moreover, Ly294002 alleviated chronic NaAsO2-induced migration and invasion in DU145 and PC-3 cells. These findings provide evidence that chronic arsenic exposure promotes migration and invasion of prostate cancer cells via an EMT mechanism driven by the AKT/GSK-3β/β-catenin/TCF4 signaling axis. Akt is expected to be a potential therapeutic target for chronic arsenic exposure-mediated prostate cancer metastasis.